Extreme dwelling: assembling domus horribilis - Campbell, Elaine (Crime, media, culture, 2022)
10 Rillington Place names the site of temporally extensive practices of murder (1943-1953), and offers an empirical entry point for critically advancing the conceptual innovations of relational approaches to the criminological study of ‘home’. In so doing, the paper, firstly, (re)conceptualises serial homicide as practice, more specifically as a mode of domestic labour which materialises in and is enacted through the relational dynamics of everyday residential life; and secondly, rejects the notion of ‘home’ and argues for the concept of dwelling to better capture the active, generative and fluid dynamics of domestic life. This subtle shift in conceptual approach acknowledges how domus horribilis is etched from, and woven through the topological entanglements of everyday and extreme practices, and moves us toward an alternative set of conceptual commitments in our research of domestic space. Drawing from a mixed portfolio of cultural media (including archival, epistolary, journalistic, photographic, filmic, architectural, museological and dramaturgical data), the paper takes forward Schatzki’s site ontology as an organising framework for practice-based analytics, and advances the critical insights of an embryonic criminology of the domestic.